Development of Blended Learning Designs using Moodle to Support Academics of The Curriculum in University of Bengkulu - Sheren Dwi Oktaria; Rambat Nur Sasongko; Muhammad Kristiawan (Jurnal Studi Guru dan Pembelajaran, 2021)
The aim of this study is to create a high-quality blended learning model using moodle and an ADDIE development step. This research results in a blended learning model based on components and learning model tools, as well as an e-learning moodle guide for lecturers and students. Based on expert validation assessments, the resulting blended learning model is of great quality. This blended learning model can help teachers navigate the complexities of BL, such as the integration process and navigation of essential learning activities and seek to involve, prepare, and support learning that has integrated online learning and F2F learning activities. Blended learning products are also developed to make it easier for lecturers to implement blended learning into the learning process and to make it easier for students to participate in learning activities according to the components of blended learning.